Предмет: Математика,
автор: MaXiM456
Решите уравнение
3(2x - 1) + 7(x - 5) = 16 + 3(1 - 2x)
Ответы
Автор ответа:
0
3(2x - 1) + 7(x - 5) = 16 + 3(1 - 2x)
6x-3+7x-35=16+3-6x
6x+7x+6x=16+3+3+35
19x=57
x=57:19
x=3
6x-3+7x-35=16+3-6x
6x+7x+6x=16+3+3+35
19x=57
x=57:19
x=3
Автор ответа:
0
красава
Автор ответа:
0
только у кого правильный
Автор ответа:
0
у меня
Похожие вопросы
Предмет: Математика,
автор: yfhutcgyik0764897
Предмет: Алгебра,
автор: shkalkagovno
Предмет: Математика,
автор: zauynbaevaaktoty
Предмет: Математика,
автор: kemepl